Enhancing critical thinking skills and media literacy in initial vocational education and training via self-nudging: The contribution of NERDVET project - Sartori, Riccardo; Tommasi, Francesco; Ceschi, Andrea; Falser, Mattia; Genero, Silvia; Belotto, Silvia (Frontiers in Psychology, 2022)
Vocational Education and Training (VET) programs are fuelled by technical and practical educational modules. The teaching staff adopts both traditional and innovative pedagogical frameworks to increase the generalization and maintenance of practical skills. At the same time, VET teachers and trainers have a few occasions to promote and include disciplines and educational programs for enhancing students’ soft skills, e.g., critical thinking skills (CT) and media literacy (ML). Following the European VET framework and literature of the field, CT and ML represent a social challenge that requires even more efforts by academics, practitioners, and policymakers. The present paper situates into this context with the aim of introducing a novel educational approach for supporting teaching staff in the promotion of students' CT and ML. This educational approach has been realized by the team of researchers and trainers of the NERDVET project, an Erasmus+ KA3 project devoted to the promotion of new tools and policies for enhancing CT and ML in VET. To pursue this aim, the team has employed the self-nudging model which regards the individuals’ set of cognitive and behavioural strategies that individuals can develop to target a specific objective. By framing pedagogical strategies into this perspective, the team realized an initial approach for educational activities and teaching strategies to promote students’ CT and ML.